Il Weltbürgerrecht nel lessico filosofico tedesco: le prime occorrenze e l’innovazione kantiana - Roberta Picardi (Lexicon Philosophicum)
The essay aims at shedding light on the innovation that Kant’s concept of Weltbürgerrecht represents – moving from an examination of the hitherto ignored pre-Kantian occurrences of the term. The starting point will be an analysis of the different meanings with which the lemma is used in non-philosophical works which, although dealing with disparate topics, share significantly the direct or indirect reference to different forms of cross-border movements (§1). In the central part, attention will focus on the most significant pre-Kantian occurrence, contained in the German translation of a French natural law treatise: the third volume of the Science du gouvernement by the French jurist Gaspard de Réal de Curban (§2). In conclusion, we will reconsider – in the light of the background outlined – Kant’s notion of Weltbürgerrecht, in order to highlight the conceptual twist that Kant gives to the expression and the eccentric stance he takes in the modern debate on the right of hospitality, by identifying cosmopolitan right and universal right to hospitality (§3).